The Impact of Climate Change on Rainfall Variability in Northern Iraq for Dry and Wet Years - Lutfah, Dr. Abdul-Abbas Awad (Thi Qar Arts Journal, 2025)
Climate change is currently the most important and urgent issue facing the international community. It is one of the most significant problems the world is dealing with today. Climate change has caused serious and potentially permanent changes to our planet, including climatic changes that have led to hydrological and biological alterations in ecosystems in general, and a decrease in rainfall and water scarcity in particular. Given the potential future impacts and serious consequences of climate change, including the drying up of some rivers and lakes, this research addresses the amount of rainfall over the stations of Erbil, Mosul, and Sulaymaniyah, and calculates the dry and wet years for the period from 1989 to 2022 according to the Standardized Precipitation Index (SPI) and standard deviation. It also examines the implications of reduced rainfall on the surface waters of the Tigris River and its tributaries in northern Iraq. The study found that the recent decades have seen lower amounts of rainfall over the research stations, and the 33-year study period was characterized by more frequent dry years compared to wet years.